QUALITY OF WORK LIFE AND TURNOVER INTENTION IN NURSES: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Ratnawati, Yuni; Bagis, Fatmah; Suyoto, Suyoto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
With the high level of turnover intention in Purwokerto type C hospitals, which reaches 15-20% per year, researchers are interested in finding out more about the influence of quality of work life on turnover intention, organizational commitment on turnover intention, and whether there is a mediating effect from organizational commitment to turnover intention. The sampling technique uses convenience sampling. The research was conducted using Partial Least Square analysis. The results of sampling were 128 nurses from 4 type C hospitals in Purwokerto. Distribution is carried out evenly according to the convenience method. The majority of respondents are female. Dominated by special nurses. Age 20-25 years. Has a diploma (D3), and is married. By using a significance level of 5%, the results of the oalysis calculations prove that organizational commitment has a significant negative effect on turnover, quality of work life has a negative but not significant effect on turnover intention, and quality of work life has a positive and significant effect on organizational commitment. This means that the relationship between quality of work life and nurses' turnover intentions is partially mediated by organizational commitment. Keywords: Quality Of Work life, Turnover Intention, Organizational Commitment